ANALISIS PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN OUTSOURCING - Beta Asteria; Priatna Dwiyansa Dwiyansa (Universitas Sarjanawiyata Tamansiswa, 2021)
Achieve the company's goals, the management of potential human resources will affect employee performance which in turn will affect the company's performance. To be able to show the performance of the employees of PT. SJS Yogyakarta Branch. companies are required to enforce motivation and work discipline on performance employee. This study will discuss the effect of motivation and work discipline on the performance of employees of outsourcing PT. SJS Yogyakarta Branch. The purpose ofThis research is: 1) Knowing the effect of motivation on employee performance outsourcing PT. SJS Yogyakarta Branch, 2) Knowing the effect of work discipline on employee performance outsourcing PT. SJS Yogyakarta Branch, 3) To determine the effect of motivation and work discipline on employee performance outsourcing PT. SJS Yogyakarta Branch. The research location at PT. SJS Yogyakarta Branch andpopulation is 87 all employees at PT. SJS Yogyakarta Branch. Sample amountof 87 respondents were taken by simple random probability sampling method. Data is analyzed using hypothesis testing. The results obtained in this study are: (1) motivation has a positive and significant effect on employee performance, (2) work discipline has a positive and significant effect on employee performance employee performance, (3) motivation and discipline have a positive and significant effect on employee performance. Keywords : Employee Performance, Motivation, Work Discipline